Operation Cleansweep for Pesticides - Frederick M. Fishel (EDIS)
This fact sheet explains the Florida Department of Agriculture and Consumer Services' Operation Cleansweep for Pesticides. This document is PI-48, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: June 2005.